ZOROASTRIANISM RELIGION TO THE BODY ARRIVAL (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article discusses the significant importance of Zoroastrianism in the ancient world in Central Asia. Scientists claim that the Avesta originated in Central Asia, in particular in Khorezm, in the 1st half of the 1st millennium BC. Zoroastrianism is the first prophetic and the first monotheistic religion in the history of mankind. It received its name from its patron, Zarathushtra, which means "having a golden camel"; there is another transcription of the name of the prophet, Zarathushtra: "zar" - Old Persian and Old Turkic - "gold" and "stur" - camel, that is, "golden camel".